Ecology of mammals and implication on park management - Ahmad Bakri, Faiznur Ain (2023)
Lack of current checklist and ecological knowledge are drawbacks for conservation and management efforts of wildlife in a protected area, such as Taman Negara Johor Gunung Ledang (TNJGL). This research aims to make TNJGL a successfully managed protected area based on results of current research, leading to sustainable conservation of biodiversity. The objectives of this research are to i) document the diversity, distribution and activity patterns of mammals along five trails in Gunung Ledang by using camera trapping, ii) translate the ecological information of mammalian fauna in TNJGL and coming up with a recommendation of wildlife management of the park, and iii) determine priority areas to conserve based on the results obtained from the sampling, interviews and reviews of document. This study employs an intensive camera trapping methodology along altitudinal gradient of five different trails. In total, 60 camera traps were set up, yielding 4245 videos in a span of 24 months. To formulate recommendations and determine priority areas for conservation, occupancy analysis was conducted, accompanied by a review of relevant documents, management plans and reports. From this research, 31 species of terrestrial mammals were recorded and together with previous findings produces the current checklist for TNJGL comprising of 60 mammal species. Mammals such as the Leopard (Panthera pardus), Sumatran Serow (Capricornis sumatraensis), and Malayan Tapir (Tapirus indicus) are recorded providing evidence of the presence of these rare species thriving in TNJGL. Using the occupancy analysis, areas to be prioritized for mammals’ conservation were presented in a map. Other than that, six issues were identified; conservation, lack of current database and information, the need to enhance TNJGL prescribed activities (CEPA and tourism), the need to upskill training of staff, enforcement and problems with wildlife. Results obtained from analyses of data, add on to the better understanding of mammal ecology in the park. Based on these results as well as taking into account the resources available, recommendations were made to address the six issues identified